Determinants of customer citizenship behaviour in Pakistan aviation sector of Pakistan - Raza, Mohsin (2020)
There is a rising interest in aviation sector branding strategies to gain customers’ supportive behaviour and loyalty towards a brand. It is important to know how branding strategies influence customers’ loyalty, and how to appeal to them to adopt citizenship behaviour. Therefore, the aim of the study was to investigate the relationship between brand experience (BE), brand image (BI), and brand awareness with customer citizenship behaviour (CCB) with the mediation effect of brand loyalty (BL). This study assumed that brand experience (BE), brand image (BI), brand awareness and brand loyalty contribute towards the adoption of CCB. The study was based on the stimulus organism response theory (SOR) to fill the gap between branding strategies and customer citizenship behaviour. For this purpose, data was collected from 377 respondents through the systematic intercept survey at the major airports of Pakistan. The data was analysed by using the Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings of the study reveal a significant relationship between brand experience towards brand loyalty and CCB with the mediation effect of brand loyalty. Brand image also has a significant relationship between brand loyalty and CCB with the mediation effect of loyalty. Brand awareness is insignificant with brand loyalty and also with CCB with the mediation effect of loyalty. The study concludes with a discussion on its contributions, and recommendations, and provides limitations as well as suggestions for future studies.